Climatic classification for the districts of Botucatu and São Manuel, SP - da Cunha, Antonio Ribeiro [UNESP] (2009)
Climatic classification defines the geographical limits of different climate types all over the world, and it is considered essential to study similar areas. This work updates the climatic classification of the municipal districts of Botucatu and of São Manuel, State of Sao Paulo, where the experimental farms of the Schools of Agronomical Sciences - UNESP, Campus of Botucatu, State of São Paulo, are located. Koppen's and Thornthwaite's methods were used for the air temperature and precipitation data, in a 36-year period (from 1971 to 2006). For both municipal districts of Botucatu and São Manuel, the climate was characterized as being Cfa, hot climate with rains in the summer and drought in the winter, and the average temperature in the hottest month is above 22 °C. According to Thornthwaite's classification, there was a small difference due to the humidity index, characterized as B2rB′3a′ (humid climate with small hydro deficiency - April, July and August, with annual potential evapotranspiration of 945.15 mm and concentration of the potential evapotranspiration in the summer of 33%) in the district of Botucatu, and as B1rB′3a′ (humid climate with small hidric deficiency - April, July and August, with annual potential evapotranspiration of 994.21 mm and concentration of the potential evapotranspiration in the summer of 33%)in the district of São Manuel.